HUBUNGAN KECUKUPAN GIZI, AKTIVITAS FISIK, DAN RIWAYAT DIARE DENGAN TINGKAT KECERDASAN INTELEKTUAL PADA ANAK LAKI-LAKI - Ayudya Anjani; Melly Kristanti; Niniek Hardini; Muttia Amalia (Poltekkes Kemenkes Semarang, 2026)
Intellectual development in school-aged children was influenced by nutritional adequacy, physical activity, and health history, yet limited studies explored their combined impact in Indonesian primary school settings. This study investigated relationships between nutritional adequacy, physical activity, diarrhea history, and intellectual intelligence levels among 41 male elementary students aged 9-12 years at SDN 04 Bojongsari Depok. Male participants were specifically selected to reduce variability related to sex differences, as boys generally demonstrate higher physical activity levels, greater nutritional requirements, and a higher incidence of diarrhea compared to girls. Samples selected via stratified random sampling based on grade level. The relatively small sample size was due to the limited number of eligible participants who met the inclusion criteria during the study period. Nutritional adequacy was assessed using the Semi-Quantitative Food Frequency Questionnaire (SQFFQ) for macro- and micronutrients, physical activity via the Physical Activity Questionnaire for Children (PAQC), both questionnaire was measured using the Indonesian version and has been commonly used among Indonesian school-aged children to estimate dietary intake. Diarrhea history through a researcher-designed questionnaire, consisting items related to the frequency and duration of diarrhea episodes during the previous one year. All items were declared valid, with r-table value of 0.3081. Reliability testing showed a Cronbach’s alpha coefficient of 0.896, indicating excellent internal consistency. Intellectual intelligence was assessed using the Indonesian version of the Culture Fair Intelligent Test (CFIT). The test was administered by a trained psychologist following standardized testing procedures. Data analysis employed Spearman correlation tests with significance at p<0,05. No significant relationships were found between macronutrient adequacy (p=0,953, r=+0,010), micronutrient adequacy (p=0,133, r=+0,239), physical activity (p=0,625, r=+0,079), or diarrhea history (p=0,650, r=-0,073) and intellectual ability. The observed correlations were weak, suggesting minimal practical influence of these variables on intellectual ability in this study population. Nevertheless, the findings should be interpreted cautiously, as other factors such as learning environment and socioeconomic status were not evaluated.